Regulatory and Operational Impacts on Indonesia’s Shipbuilding Costs - Handoko, Wisnu; Setiawan, Ariyono; Suwondo, Iie; Widjanarko Otok , Bambang; Wou Onn, Choo (Jurnal Penelitian Transportasi Laut, 2025)
Regulatory and Operational Impacts on Indonesia’s Shipbuilding Costs: This study aims to quantify the impact of regulatory and operational delays on shipbuilding costs in Indonesia, a maritime nation undergoing rapid infrastructure modernization. Grounded in the theoretical frameworks of institutional economics and project risk management, the research investigates how permit duration and project delays affect the financial performance of nationally significant vessel construction projects. Employing a quantitative approach, data from 14 real-world shipbuilding projects including patrol boats, offshore patrol vessels (OPVs), tankers, and submarines were analyzed. Key variables comprised total project cost (in billion IDR), permit time (months), and project delay duration (weeks). Descriptive statistics, Pearson correlations, and multiple linear regression were performed, followed by robust regression and outlier diagnostics (Cook’s Distance and VIF analysis) to ensure model reliability. The results reveal that project delays significantly increase total costs (p < 0.001), whereas permit duration exhibits a negative but context-dependent relationship. The model explains 68% of cost variation (R² = 0.68), with multicollinearity between permit time and delays (r = 0.94) indicating the need for cautious interpretation. Robust regression and diagnostic tests confirm the influence of high-cost defense projects as outliers. These findings provide actionable insights for maritime infrastructure policy, highlighting the need to streamline permit procedures, enhance inter-agency coordination, and mitigate project execution delays. This research contributes novel empirical evidence from real project data and applies advanced diagnostic techniques, addressing a critical gap in Southeast Asian maritime economics literature.